A New Bis-Coumarin from the seeds of Colvillea racemosa - Sreenath, D.; Rao, J.T. (Asian Journal of Chemistry, 2010)
The new bis-coumarin, 6-methoxy-7-hydroxy bis-coumarin (1) was isolated from the seeds of Colvillea racemosa.